2005
DOI: 10.1017/s0950268805005509
|View full text |Cite
|
Sign up to set email alerts
|

Most Campylobacter subtypes from sporadic infections can be found in retail poultry products and food animals

Abstract: The subtypes of Campylobacter isolates from human infections in two Danish counties were compared to isolates from retail food samples and faecal samples from chickens, pigs and cattle. During a 1-year period, 1285 Campylobacter isolates from these sources were typed by two methods: 'Penner' heat-stable serotyping and automated ribotyping (RiboPrinting). C. jejuni was the dominating species, but C. coli was more prevalent among food and chicken isolates (16%) compared to human isolates (4%). In total, 356 diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 24 publications
4
44
0
Order By: Relevance
“…Several other studies also have reported a 34 to 60% overlap between serotypes, genotypes, and/or sequence types (STs) of patient and poultry isolates using various typing techniques (20,31,37,42).…”
mentioning
confidence: 98%
“…Several other studies also have reported a 34 to 60% overlap between serotypes, genotypes, and/or sequence types (STs) of patient and poultry isolates using various typing techniques (20,31,37,42).…”
mentioning
confidence: 98%
“…Poultry sources have not accounted for 100% of human infections, and typing surveys have found human Campylobacter strains that do not exhibit similarity (do not cluster) with poultry strains (7,26,27,32,33). Cattle and human Campylobacter isolates have been found to be similar using a variety of molecular typing methods (5,22,33), and typing studies have suggested that cattle may play a role in the epidemiology of campylobacteriosis (5,26,33). In a study by Nielsen et al, human and cattle C. jejuni isolates were identical based on six molecular typing methods (31).…”
mentioning
confidence: 99%
“…The detection of C. jejuni in a ground beef sample was unusual. This isolate was indistinguishable by multiple typing methods from one human isolate and closely related to three additional isolates, strongly suggesting that ground beef is a source of human infection with C. jejuni (8,38), especially in the absence of detection of the same type in chicken or any other source. The data presented in the current study support a growing opinion that cattle contribute significantly in some way to the burden of human disease caused by Campylobacter (26,39).…”
Section: Discussionmentioning
confidence: 83%